Pelatihan Pembuatan Poster Kreatif Untuk Meningkatkan Kemampuan Komunikasi Visual Anak - Tamara, Fetrilissa Ayu; Sinambela, Hema Desti Aningsih; Ridho Daffa Fadilah; Rini Wana Lumban Gaol; Reni Nur Eriyani (CV Putra Publisher, 2024)
Poster making training is carried out to improve children’s visual communication skills and the importance of instilling a culture of saving literacy in children from an early age, so this is our effort to teach children about the importance of managing money well and wisely from an early age. In addition, the purpose of this training is to teach children the importance of instilling a culture of saving literacy from an early age to teach children about the importance of managing money well and wisely from an early age. The method of community service used is a lecture on the importance of saving and information about making posters. This activity is carried out face to face. This activity is focused on increasing awareness of saving in children. In this activity, children directly become aware of the concept of saving from the words of the posters they compose. The methods in this study are lectures, tutorials, practice and presentations. Based on the results of this study, children have shown the ability to understand the contents of posters and make posters with the selection of words and images that are in accordance with the theme of saving